Geochemistry, mineralogy, and 40K-40Ar radiometric dating of DSDP Leg 84 basalts - Guatemala Trench - Bellon, Herve; Maury, R C; Joron, Jean Louis; Bourgois, Jacques; Aubouin, Jean (Supplement to: Bellon, H et al. (1985): Geochemistry, mineralogy, and 40K-40Ar radiometric dating of Leg 84 basalts - Guatemala Trench. In: von Heune, R; Aubouin, J; et al. (eds.), Initial Reports of the Deep Sea Drilling Project, Washington (U.S. Govt. Printing Office), 84, 655-663, https://doi.org/10.2973/dsdp.proc.84.122.1985, 1985)
Geochemical (atomic absorption, neutron activation analyses), mineralogical (microprobe), and radiometric (40K - 40Ar) data are presented for five basalts from the Guatemala Trench area (Deep Sea Drilling Project, Leg 84). Strong geochemical and mineralogical differences distinguish two types among these basalts: (1) One basalt (Sample 567A-19,CC), recovered below Upper Cretaceous limestone has the following characteristics: it is quartz normative and has low TiO2, content, as well as low amounts of Cr, Ni and other transition metals, an LREE depleted pattern, and affinities of clinopyroxene phenocryst plotted into the field of tholeiitic and calc-alkalic pyroxenes. (2) Four alkaline basalts, recovered from the mafic and ultramafic acoustic basement, are nepheline normative and show high TiO2 content, high amounts of Cr, Ni and so on, an LREE enriched pattern and compositions of clinopyroxene phenocryst plotted close to or within the field of alkali basalt pyroxenes. These basalts are comparable to those recognized in the lower part of the Santa Elena complex and are clearly different from the oceanic basalts of the Cocos Plate. The radiometric age of the orogenic basalt seems to be close to 80 Ma. The alkaline basalts are clearly older, even if a discrepancy appears between the results of different analyses because of the secondary effects of alteration.